2016
DOI: 10.1515/manment-2015-0067
|View full text |Cite
|
Sign up to set email alerts
|

Building resilient relationships with suppliers in the B2B market

Abstract: Summary The growing uncertainty of business environment that negatively influences the contemporary supply chains is one of the major challenges for today’s managers. The literature recommends the development of resistant supply chains, defining them as adaptive and flexible. However, there are a few scientific publications that directly link to the area of Supplier Relationship Management in this regard. The article aims to answer the question what is the flexibility and adaptability and how to perceive these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Supply chain resilience has been studied in various industries and more importantly in the food supply chains (Colwill et al ., 2016). Supplier development has been identified as one of the strategies for reducing vulnerability to food supply chain disruptions (Wieteska, 2016). In this study it is proposed that supply chain resilience as manifested via its drivers identified above can be achieved through supplier development in the form of contract farming.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Supply chain resilience has been studied in various industries and more importantly in the food supply chains (Colwill et al ., 2016). Supplier development has been identified as one of the strategies for reducing vulnerability to food supply chain disruptions (Wieteska, 2016). In this study it is proposed that supply chain resilience as manifested via its drivers identified above can be achieved through supplier development in the form of contract farming.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Flexibility is generally decomposed into supplier flexibility, procurement flexibility, and logistic flexibility. Supplier flexibility refers to a supplier's ability to respond effectively to changes in customers' orders in terms of volume, product mix, and delivery (Wieteska, 2016). This ability to be flexible is enhanced when suppliers are capacitated through the provision of resources.…”
Section: Supply Chain Flexibilitymentioning
confidence: 99%
“…According to Zolkiewski et al (2006), adaptation refers to the “extent to which buyer and seller make a substantial investment in the relationship” and the “exchange of specific investment is the adaptation” (Su et al , 2008). Accordingly, Wieteska (2016) views adaptation as a core tenet of any working business relationship and helps firms to adjust to significant environmental changes. Adaptation is known to include product and process design, delivery systems, value analysis, quality control and cost targeting (Su et al , 2008).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…It also embraces a resilient construction sector and its supply chains. Small and medium-sized enterprises should strengthen their resilience to distortions to ensure continuity of their operations and market competitiveness (Gayan et al, 2010;Wieteska, 2016). We also need new technologies and innovation supporting construction sector adaptation, new services and industries, as well as new adaptation jobs.…”
Section: Climate Change Adaptation In Real Estate Sector: Findings Of Literature Reviewmentioning
confidence: 99%